Desenvolvimento de um software pré-processador gráfico para análise de transitórios em subestações - Marchesan, Adriano Cavalheiro (2016)
The following work presents a graphical pre-processor software as an alternative version of the Electromagnetic Transients Program (ATP-EMTP). It was developed to aid in the analysis of electromagnetic transients in power substations. The software has been developed using Java programming language and it was named Alternative Transients Program Substation Analysis (ATP-SA). Amongst its functionalities, it can be highlighted the representation of precursory events of electromagnetic transients in the ATP-EMTP standard, data predefinition for the modeling of these events, simulation configuration with compatible values in reference to the transient phenomena to be studied and management simulation through a databank. The transients to be considered are: occurrence and clearance of faults, transformer inrush, Transient Recovery Voltage (TRV) in circuit-breakers, circuit-breaker switching and lightning surges. The software aids in the simulation of transients occurred by these events in both deterministic and stochastic ways. In addition, to show its potentialities, examples of application are presented in a real power system simulations. Hence, with the use of the mentioned software, it is expected to support in subsidies and safety with respect of operations in substations, as well to aid in defect prevention, loss of equipment and potential shutdowns. This work is the main theme of a Research and Development (R&D) project developed by the Laboratory of Analysis and Protection of Power Systems, in the Power System and Energy Research Center, in a partnership along with the State Company of Generation and Transmission of Electric Energy of the Rio Grande do Sul State.